Posisi Perempuan Etnis Minangkabau dalam Dunia Patriarki di Sumatera Barat dalam Perspektif Agama, Keluarga dan Budaya - Valentina, Tengku Rika; Putra, Roni Ekha (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2008)
Culturally and socially, Minangkabau women, or well known as Bundo Kanduang, has a typical position in Minangkabau traditional law. The economic resources and its use, actually, is focused to the women and it is being supported when they have to deal with political context, primarily in traditional community, where the women rights in order to aim the consensus. It is very significant to determine the result that willing to achieve. Kata Kunci: Budaya Patriarki, Kelompok Etnik, Etnik Minangkabau, Matrilinial